2015
DOI: 10.1002/cmdc.201500497
|View full text |Cite
|
Sign up to set email alerts
|

Small‐Molecule and Peptide Inhibitors of the Pro‐Survival Protein Mcl‐1

Abstract: The ability of protein–protein interactions to regulate cellular processes in both beneficial and detrimental ways has made them obvious drug targets. The Bcl‐2 family of proteins undergo a series of protein–protein interactions which regulate the intrinsic cell‐death pathway. The pro‐survival members of the Bcl‐2 family, including Bcl‐2, Bcl‐xL, and Mcl‐1, are commonly overexpressed in a number of human cancers. Effective modulators of members of the Bcl‐2 family have been developed and are undergoing clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
36
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 103 publications
(96 reference statements)
0
36
0
Order By: Relevance
“…Mcl‐1 is an antiapoptotic protein that belongs to the Bcl‐2 family. It is over‐expressed in many cancer cell types leading to resistance to apoptosis as well as to resistance of chemo‐ and radiotherapies (Beekman & Howell, ). Recently, inhibition of Mcl‐1 via small molecule inhibitors has become of interest (Belmar & Fesik, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mcl‐1 is an antiapoptotic protein that belongs to the Bcl‐2 family. It is over‐expressed in many cancer cell types leading to resistance to apoptosis as well as to resistance of chemo‐ and radiotherapies (Beekman & Howell, ). Recently, inhibition of Mcl‐1 via small molecule inhibitors has become of interest (Belmar & Fesik, ).…”
Section: Discussionmentioning
confidence: 99%
“…Error bars represent the standard error of the mean. Data for 6 Gy not shown to resistance to apoptosis as well as to resistance of chemo-and radiotherapies (Beekman & Howell, 2016 Considering that treatment options for head and neck cancer include radio-and chemotherapy, the combinatorial effect of 6-shogaol with irradiation and cisplatin was examined. A combination of treatment modalities often leads to major side effects and a significant reduction in quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Ar ecent review on Mcl-1 inhibitors highlights that less than thirty compounds have been reported with comparable selectivity for Mcl-1. [28] Further studies are underway to structurally confirm the binding sites of the hybrid and small-molecule compounds generated from peptide-directed binding.I ti se xpected that peptide-directed binding is applicable to other a-helical PPIs,s uch as the p53/hDM2 interaction, the Bcl-x L /BIM interaction, or the HIV gp41 hexameric coiled-coil fusion complex. [29] …”
Section: Protein-proteininteractions(ppis)regulatemanyprocessesmentioning
confidence: 99%
“…Ar ecent review on Mcl-1 inhibitors highlights that less than thirty compounds have been reported with comparable selectivity for Mcl-1. [28] Further studies are underway to structurally confirm the binding sites of the hybrid and…”
Section: Protein-proteininteractions(ppis)regulatemanyprocessesmentioning
confidence: 99%
“…Importantly, these compounds are able to mimic the selectivity of the natural scaffold. A recent review on Mcl‐1 inhibitors highlights that less than thirty compounds have been reported with comparable selectivity for Mcl‐1 28. Further studies are underway to structurally confirm the binding sites of the hybrid and small‐molecule compounds generated from peptide‐directed binding.…”
mentioning
confidence: 99%